2012
DOI: 10.5194/angeo-30-1451-2012
|View full text |Cite
|
Sign up to set email alerts
|

Interball-1 observations of flux transfer events

Abstract: Abstract. We present the results of a survey of 807 FTEs observed by Interball-1 on the mid-and high-latitude dayside and flank magnetopause. Dayside magnetosheath events show a strong tendency to occur for southward magnetosheath magnetic fields suggesting origin via component (or perhaps antiparallel) reconnection near the equatorial plane. Flank FTEs occur for both magnetosheath magnetic field orientations with only a slight preference for southward magnetosheath magnetic fields. These events are consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The distribution of these normalized core field strengths is shown in Figure d. Whereas the core field of FTEs at Earth rarely exceeds 50 nT [ Wang et al , ; Korotova et al , ], some of the FTEs in this study have core fields of up to 400 nT, or 160% of the field strength just inside the magnetopause. By comparison, the typical ~1–2 nPa solar wind at 1 AU would produce a magnetic field intensity at Earth's magnetopause of ~50 to 70 nT.…”
Section: Modeling and Analysismentioning
confidence: 71%
See 2 more Smart Citations
“…The distribution of these normalized core field strengths is shown in Figure d. Whereas the core field of FTEs at Earth rarely exceeds 50 nT [ Wang et al , ; Korotova et al , ], some of the FTEs in this study have core fields of up to 400 nT, or 160% of the field strength just inside the magnetopause. By comparison, the typical ~1–2 nPa solar wind at 1 AU would produce a magnetic field intensity at Earth's magnetopause of ~50 to 70 nT.…”
Section: Modeling and Analysismentioning
confidence: 71%
“…Wang et al [] showed an asymmetry between the number of FTEs observed in the dawn and dusk sectors at Earth, but they ruled out the Parker spiral IMF sector as the cause of this asymmetry. Subsequent studies [e.g., Fear et al , ; Korotova et al , ] indicated that the location of the reconnection site(s) and the subsequent motion of the FTEs are governed primarily by the orientation of the magnetic field in the magnetosheath.…”
Section: Modeling and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…FTEs have been observed at Earth at all locations on the magnetopause under a wide range of solar wind conditions by single spacecraft such as International Sun‐Earth Explorer 1 (ISEE 1) (Kawano & Russell, , ) and Interball‐1 (e.g., Korotova et al, ; Sibeck et al, ), in addition to many multispacecraft missions, including Cluster (e.g., Fear et al, ), Time History of Events and Macroscale Interactions during Substorms (THEMIS) (e.g., Korotova et al, ; Trenchi et al, ), and most recently Magnetospheric Multiscale (MMS) (e.g., Eastwood et al, ; Farrugia et al, ; Hasegawa et al, ), allowing for accurate determination of the orientation and scale size of the FTEs. Such detailed measurements are not possible with the single MESSENGER spacecraft; however, observations have nonetheless not only confirmed the presence of FTEs at Mercury but also shown them to be ubiquitous in nature (Imber et al, ; Slavin, Anderson, et al, ; Slavin, Lepping, et al, ; Slavin et al, , ).…”
Section: Introductionmentioning
confidence: 99%